2012
DOI: 10.1128/jb.00120-12
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Serotype O55:H7 Diversity Supports Parallel Acquisition of Bacteriophage at Shiga Toxin Phage Insertion Sites during Evolution of the O157:H7 Lineage

Abstract: bEnteropathogenic Escherichia coli (EPEC) continues to be a leading cause of mortality and morbidity in children around the world. Two EPEC genomes have been fully sequenced: those of EPEC O127:H6 strain E2348/69 (United Kingdom, 1969) and EPEC O55:H7 strain CB9615 (Germany, 2003). The O55:H7 serotype is a recent precursor to the virulent enterohemorrhagic E. coli O157:H7. To explore the diversity of O55:H7 and better understand the clonal evolution of O157:H7, we fully sequenced EPEC O55:H7 strain RM12579 (Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 81 publications
(107 reference statements)
6
64
0
Order By: Relevance
“…We did not observe prophages with high sequence similarity to Sp11 and Sp12 in the corresponding genomic region of E. coli O55:H7 (see Fig. S4), the predecessor of O157:H7 (19,(44)(45)(46). These observations collectively highlighted the dynamic changes within this region that have occurred during the course of O157:H7 evolution.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We did not observe prophages with high sequence similarity to Sp11 and Sp12 in the corresponding genomic region of E. coli O55:H7 (see Fig. S4), the predecessor of O157:H7 (19,(44)(45)(46). These observations collectively highlighted the dynamic changes within this region that have occurred during the course of O157:H7 evolution.…”
Section: Discussionsupporting
confidence: 54%
“…Although in silico analysis suggested that many of these prophages are defective, Asadulghani et al (15) demonstrated that some can be induced or packaged and may even transduce other E. coli strains. The constant loss and acquisition of prophages are identified as the major mechanisms in the evolution of this pathogen (11,12,15,(18)(19)(20). In addition to integrase-mediated phage integration and excision, homologous recombination between related prophages can also contribute to the genomic instability of E. coli O157:H7 (9,11).…”
mentioning
confidence: 99%
“…We found no similarities between this sequence and those of any other replication proteins from known Inc group plasmids (33,45). GenBank analysis showed that RCS47 RepA is present in only the genomes of phages, such as pO111_2 (46) and p12579_1 (47), with which it displayed 99% and 100% identity, respectively, at the protein level. The IncY replicon mobile elements associated with strains producing ESBL genes have been described in several epidemiologic studies (19,48,49) but, unlike RCS47 RepA, the IncY replicon is found on both phages and plasmids (10; T. Billard-Pomares and C. Branger, unpublished data).…”
Section: Resultsmentioning
confidence: 86%
“…The stepwise evolution of GUD Ϫ SOR Ϫ O157:H7 strains from an O55:H7 ancestor has been described in great detail (6)(7)(8)(9)(10). At least one genome sequence from each proposed evolutionary node (except for 9.1a and 9.2e) is available, permitting for the first time the ordered reconstruction of CRISPR dynamics in E. coli over a several-thousand-year span (10).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most wellknown and studied STEC strains is E. coli O157:H7. This serotype evolved from an O55:H7 ancestor, and a stepwise evolutionary model was proposed and updated in several studies (6)(7)(8)(9)(10). The non-O157 STEC strains, on the other hand, are underreported due to limitations in laboratory isolation and detection methods.…”
mentioning
confidence: 99%